2015
DOI: 10.1071/rd13198
|View full text |Cite
|
Sign up to set email alerts
|

Subpopulation pattern of eel spermatozoa is affected by post-activation time, hormonal treatment and the thermal regimen

Abstract: CSIRO PublishingGallego Albiach, V.; Vilchez Olivencia, MC.; Peñaranda, D.; Pérez Igualada, LM.; Herraez, MP.; Asturiano Nemesio, JF.; Martinez-Pastor, F. (2015). The subpopulation pattern of eel sperm is affected by post-activation time, hormonal treatment and thermal regime. Reproduction, Fertility and Development. 27(3):529-543. doi:10.1071/RD13198. Natural stocks of eels (genus Anguilla) have suffered a dramatic reduction in the last 60 years, and 16 aquaculture is based in the capture of huge quantities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 51 publications
2
26
0
2
Order By: Relevance
“…Previously, the whole population of spermatozoa in an ejaculate has been considered; as it was described by a normal distribution model, spermatozoa were considered as equivalent, with the same chances of being “selected” for fertilization. Nevertheless, by considering the quantitative data obtained from CASA systems, different authors have proposed that the actual distribution of sperm cells is not uniform, not normally distributed but structured in well‐defined subpopulations, (Amann & Hammerstedt, ; Caldeira et al., ; Gallego et al., ; Hirai et al., ; Soler et al., ; Thurston, Watson, Mileham, & Holt, ; Valverde et al., ; Vásquez et al., ; Yániz et al., , ). Even today, in the boar, a relationship between these subpopulations and the fertilizing capacity of the ejaculates has been established (Abaigar et al., ; Holt et al., ; Vyt et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the whole population of spermatozoa in an ejaculate has been considered; as it was described by a normal distribution model, spermatozoa were considered as equivalent, with the same chances of being “selected” for fertilization. Nevertheless, by considering the quantitative data obtained from CASA systems, different authors have proposed that the actual distribution of sperm cells is not uniform, not normally distributed but structured in well‐defined subpopulations, (Amann & Hammerstedt, ; Caldeira et al., ; Gallego et al., ; Hirai et al., ; Soler et al., ; Thurston, Watson, Mileham, & Holt, ; Valverde et al., ; Vásquez et al., ; Yániz et al., , ). Even today, in the boar, a relationship between these subpopulations and the fertilizing capacity of the ejaculates has been established (Abaigar et al., ; Holt et al., ; Vyt et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect is that the correct determination of sperm tracks results in a fundamental shift in the determination of motility and morphology subpopulation structure. The fact that an ejaculate is constituted of different subpopulations of spermatozoa has been well established in a great variety of species (boar (Abaigar, Holt, Harrison, & del Barrio, ; Flores et al., ; Holt, Holt, & Moore, ; Soler et al., ), bull (Valverde et al., ; Yániz et al., ), donkey (Flores et al., ), eel (Gallego et al., ), fox (Soler et al., , ), gazelle (Abaigar et al., ), goat (Vázquez et al., ), ram (Luna et al., ), stallion (Ortega‐Ferrusola et al., ), human (Vásquez, Soler, Camps, Valverde, & García‐Molina, ; Yániz et al., ), salmon (Caldeira et al., )), but most of these studies were not designed for considering the effect of the FR.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, velocity parameters are the most widely used in aquatic species (Liu et al., ). In the last few years, it has been demonstrated that grouping spermatozoa in subpopulations on the basis of their velocity makes it possible to identify changes occurring in the semen with reference to the coexistence of different subpopulations with distinct motility characteristics within the same sample (Beirão, Cabrita, Pérez‐Cerezales, Martinez‐Pánaramo & Herráez, ; Gallego et al., ). Indeed, in the sea urchin A. crassispina , velocity parameters showed significant reduction after exposure to cadmium (Au et al., ), while in the sea bream S. aurata , cryopreservation proved to affect different sperm subpopulations in different ways (Beirão et al., ), while the relative size of the RAP sperm subpopulation was more strongly impaired by toxicants than the TM population (Fabbrocini et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Once characterized, subpopulations can be related to treatments, male differences, sperm physiology and most importantly, sperm fertility (Martínez‐Pastor, Cabrita, Soares, Anel & Dinis et al . ; Gallego, Vílchez, Peñaranda, Pérez, Herráez, Asturiano & Martínez‐Pastor ).…”
Section: Sperm Functionalitymentioning
confidence: 99%